A STUDY OF VENDOR-MANAGED INVENTORY (VMI) AND CLOUD-BASED INVENTORY MANAGEMENT TOOLS FOR MSMES IN BOISAR MIDC OF PALGHAR DISTRICT - Mohite, Rohit; Chaurasiya, Ravi; Rajawat, Anand Singh; Rodrigues, Kiran (Universitas Dian Nuswantoro, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are pivotal to India's manufacturing growth, yet they struggle with efficient inventory management due to infrastructural bottlenecks, outdated practices, and limited digital integration. This study explores the adoption potential of two transformative approaches—Vendor-Managed Inventory (VMI) and Cloud-Based Inventory Management Tools—within the industrial cluster of Boisar MIDC, Palghar District. A survey of 380 MSMEs reveals that while awareness of cloud-based systems is growing, actual implementation remains limited. VMI adoption is even lower, hindered by trust gaps and integration challenges. However, early adopters report tangible benefits including reduced lead times, improved collaboration, and operational cost savings. Using path modelling, the study confirms significant positive effects of technology adoption on manufacturing efficiency (β = 0.49) and strategic planning. These findings underscore the need for policy-backed digital training, phased technology rollouts, and stronger vendor partnerships. The study offers a scalable framework for enhancing inventory efficiency across similar industrial clusters in India.